20(S)-Ginsenoside Rg(3) is a novel inhibitor of autophagy and sensitizes hepatocellular carcinoma to doxorubicin - Kim, Dong-Gun (Impact Journals LLC, 2014)
Hepatocellular carcinoma (HCC) is the second leading cause of cancer-related deaths worldwide. High mortality from HCC is mainly due to widespread prevalence and the lack of effective treatment, since systemic chemotherapy is ineffective, while the targeted agent Sorafenib extends median survival only briefly. The steroidal saponin 20(S)-ginsenoside Rg(3) from Panax ginseng C.A. Meyer is proposed to chemosensitize to various therapeutic drugs through an unknown mechanism. Since autophagy often serves as cell survival mechanism in cancer cells exposed to chemotherapeutic agents, we examined the ability of Rg(3) to inhibit autophagy and chemosensitize HCC cell lines to doxorubicin in vitro. We show that Rg(3) inhibits late stage autophagy, possibly through changes in gene expression. Doxorubicin-induced autophagy plays a protective role in HCC cells, and therefore Rg(3) treatment synergizes with doxorubicin to kill HCC cell lines, but the combination is relatively nontoxic in normal liver cells. In addition, Rg(3) was well-tolerated in mice and synergized with doxorubicin to inhibit tumor growth in HCC xenografts in vivo. Since novel in vivo inhibitors of autophagy are desirable for clinical use, we propose that Rg3 is such a compound, and that combination therapy with classical chemotherapeutic drugs may represent an effective therapeutic strategy for HCC treatment.